Modulating Room-Temperature Phosphorescence-To-Phosphorescence Mechanochromism by Halogen Exchange - Takewaki, Yoshika; Ogawa, Takuji; Tani, Yosuke (Frontiers in Chemistry, 2022)
Modulating stimuli-responsiveness of luminescent crystals is challenging owing to the complex interdependent nature of the controlling factors, such as molecular structure, crystal structure, luminescent properties, and responsiveness thereof. Herein, we demonstrate a halogen exchange approach that disentangles the issue and realizes the modulation of room-temperature phosphorescence-to-phosphorescence mechanochromism. Namely, two halogenated thienyl diketones BrTn and ClTn with replacing Br to Cl afforded isostructural crystal, which made the molecular structure independent from the crystal structure. Consequently, the initial crystal structure, as well as the amorphization behavior against mechanical stimulation, were retained. In contrast, the molecular phosphorescence properties were modulated likely because of the different extent of the heavy atom effect. Thus, halogen exchange would be a promising approach to modulate stimuli-responsive photofunctions of crystals involving spin-forbidden processes.